The potential of the discovery learning model integrated the reading, questioning, and answering model on cross-cultural high school students’ problem-solving skills - Hariyanto Hariyanto; Siti Roudlotul Hikamah; Nasruliyah Hikmatul Maghfiroh; Endra Priawasana (Intelektual Pustaka Media Utama, 2023)
This study aims to test the discovery model integrated with the reading, questioning, and answering (RQA) model. This research is a quasi-study which involves the second semester XI grade students of state senior high school (SMA) Negeri in Situbondo as subjects. The number of students who studied was 160 people from four different classes in the 2018/2019 academic year. Sampling is done by class equality test. Each class is taught with a different model, for each class is grouped again based on the culture of residence of students, namely coastal students, urban and mountain students. Researchers used Ancova to test the research hypothesis followed by the least significant difference (LSD) test. The results showed that: i) RQA’s integrated discovery learning model is able to improve students’ problem-solving skills compared to the original model; ii) Culture has a significant role in shaping students’ problem-solving skills, with the use of the same model given to students who have a background a different background will get different results; and iii) Learning in school and in the environment is an interrelated factor in shaping students’ thinking patterns and problem-solving skills. Discovery learning model integrated learning RQA model is a combination of effective models to be applied to students who are trained with challenges where nature teaches them to think and act appropriately and quickly.